Challenger multinationals in telecommunications: Huawei and ZTE - Pawlicki, Peter (Brussels, 2017)
"This background analysis looks at the development and success of two Chinese companies, Huawei and ZTE, as major players on the global market of telecommunications equipment producers. The case of both companies indicates the importance of integrated industrial policies and can serve as a wake-up call for all policy stakeholders in the EU.